Synthesis of complex thermally coupled distillation systems including divided wall columns - Caballero, José A.; Grossmann, Ignacio E. (AIChE journal, 2013)
The design of thermally coupled distillation sequences explicitly including the possibility of divided wall columns (DWC) is described. A DWC with a single wall can be considered thermodynamically equivalent to a fully thermally coupled (FTC) subsystem formed by three separation tasks (a Petlyuk configuration in the case of three‐component mixtures). It is shown how to systematically identify all the sequences of separation tasks that can produce configurations that include at least a DWC. Feasible sequences that explicitly include DWCs are enforced through a set of logical relationships in terms of Boolean variables. These logical relationships include as feasible alternatives from conventional columns (each column must have a condenser and a reboiler) to FTC systems (only one reboiler and one condenser in the entire system). A comprehensive disjunctive programming formulation for finding the optimal solution is presented. The model is based on the Fenske, Underwood Gilliland equations. However, the disjunctive formulation allows easily the use of any other shortcut, aggregated or even rigorous model without modifying much the structure of the model. Two illustrative examples illustrate the procedure. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1139–1159, 2013